The Wilkinson Complex as a heterogeneous catalyst in the partial hydrogenation of 1-heptyne. regeneration of the complex - Cagnola, Edgardo Alberto (2016)
The Wilkinson complex was tested as a catalyst in the partial hydrogenation of 1-heptyne, a medium chain alkyne, at a temperature of T = 303 K and hydrogen pressure PH2 = 150 kPa. The tests were performed in homogeneous system as well as heterogeneous, supporting the complex on i) ã-Al2O3 and ii) a commercial arbonaceous material, RX3. Characterization by means of XPS and FTIR revealed that the anchored complex did not lose its chemical identity, being the catalytically active species. The Wilkinson complex on RX3 showed better conversions and selectivities, higher than the Lindlar catalyst, used as a reference. Additionally, it was proposed a method to recover Rh as a metal from the remaining solutions, and regenerate the complex to be reused from it.